Welcome to Molecular Brain - Mei, Lin (BioMed Central, 2008)
We are delighted to announce the arrival of a brand new journal dedicated to the ever-expanding field of neuroscience. Molecular Brain is a peer-reviewed, open-access online journal that aims at publishing high quality articles as rapidly as possible. The journal will cover a broad spectrum of neuroscience ranging from molecular/cellular to behavioral/cognitive neuroscience and from basic to clinical research. Molecular Brain will publish not only research articles, but also methodology articles, editorials, reviews, and short reports. It will be a premier platform for neuroscientists to exchange their ideas with researchers from around the world to help improve our understanding of the molecular mechanisms of the brain and mind.